Insights into molecular and metabolic events associated with fruit response to post-harvest fungal pathogens - Alkan, Noam; Fortes, Ana M. (Frontiers in Plant Science, 2015)
Due to postharvest losses more than 30% of harvested fruits will not reach the consumers’ plate. Fungal pathogens play a key role in those losses, as they cause most of the fruit rots and the customer complaints. Many of the fungal pathogens are already present in the unripe fruit but remain quiescent during fruit growth until a particular phase of fruit ripening and senescence. The pathogens sense the developmental change and switch into the devastating necrotrophic life style that causes fruit rotting. Colonization of unripe fruit by the fungus initiates defensive responses that limit fungal growth and development. However, during fruit ripening several physiological processes occur that correlate with increased fruit susceptibility. In contrast to plant defenses in unripe fruit, the defense posture of ripe fruit entails a different subset of defense responses that will end with fruit rotting and losses. This review will focus on several aspects of molecular and metabolic events associated with fleshy fruit responses induced by postharvest fungal pathogens during fruit ripening.